Hubungan Tingkat Kesepian Dengan Kualitas Hidup Pada Lansia Di Panti Jompo Tresna Werda Kota Bengkulu - Saiful Batubara; Julahir Hotmatua Siregar; Aulia Fuad (Universitas Batam, 2022)
Background : Loneliness in elderly usually caused by spouse's death, physical deterioration or limited social skill also the lack of support from family or relatives. The loneliness in elderly will effect the emotional condition, coping mechanism, or acceptance and in the end will effect the quality of life in elderly. Methods : This research is an analytic observational study with a cross sectional research design. This research was conducted at Nursing House Tresna Werda of Bengkulu in November 2021. The sample in this study was 68 respondens. The sampling technique is total sampling. To determine the relationship between Loneliness Levels and Quality of Life, the data analysis used was the Spearman rho’s. Result : From 68 respondents, elder with high stage loneliness and poor quality of life is 57 person (93,4%). The results of the Spearman rho’s statistical test obtained p value = 0,00 (p<0,05), so Ha is accepted and H0 is rejected. Conclusion : In conclusion, the findings suggest significant correlation of Loneliness Levels and Quality of Life in the Elderly in Nursing House Tresna Werda of Bengkulu Year 2021